Applying Participatory Methods to Address Motivational Aspects in Informal Workplace - Holocher, Teresa; Kieslinger, Barbara; Fabian, Claudia Magdalena (International Journal of Advanced Corporate Learning (iJAC), 2011)
Motivational aspects are core to successful knowledge sharing and collaborative learning experiences. However, it still remains one of the great challenges to overcome motivational barriers when it comes to introducing information systems for collaborative learning at the workplace. In the context of an international research project we have taken motivational aspects into account during the design phase and started a participatory process involving researchers, end-users, managers, designers and developers. As initial findings show, a continuous dialogue with end-users may contribute to creating a sense of ownership amongst them and become a motivational driver for the future use of the system.